2022
DOI: 10.1016/j.envres.2021.111765
|View full text |Cite
|
Sign up to set email alerts
|

A review of methods to reduce the probability of the airborne spread of COVID-19 in ventilation systems and enclosed spaces

Abstract: COVID-19 forced the human population to rethink its way of living. The threat posed by the potential spread of the virus via an airborne transmission mode through ventilation systems in buildings and enclosed spaces has been recognized as a major concern. To mitigate this threat, researchers have explored different technologies and methods that can remove or decrease the concentration of the virus in ventilation systems and enclosed spaces. Although many technologies and methods have already been researched, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0
9

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 93 publications
(202 reference statements)
1
59
0
9
Order By: Relevance
“…It is essential to reduce long-term risks from this novel virus until we understand them better, as well as reduce the risk of new variants emerging by suppressing transmission. There is now extensive evidence that transmission can be reduced through widespread use of face masks [ 78 , 79 , 80 , 81 ], better ventilation [ 82 ] and air filtration [ 83 ]. Contact tracing and isolation are established and effective methods of reducing transmission.…”
Section: Discussionmentioning
confidence: 99%
“…It is essential to reduce long-term risks from this novel virus until we understand them better, as well as reduce the risk of new variants emerging by suppressing transmission. There is now extensive evidence that transmission can be reduced through widespread use of face masks [ 78 , 79 , 80 , 81 ], better ventilation [ 82 ] and air filtration [ 83 ]. Contact tracing and isolation are established and effective methods of reducing transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Several works and research projects have already shown that enclosed spaces are infection grounds for COVID-19 [27][28][29][30][31][32]. The Department of Education of England will spend 25 million pounds installing 300,000 CO 2 monitors in classrooms in state schools and colleges.…”
Section: Related Workmentioning
confidence: 99%
“…The society of Heating, Air-Conditioning and Sanitary Engineers of Japan (SHASE) [5], as well as American Society of Heating, Refrigerating and Air-Conditioning Engineers (ASHRAE) [6] and Federation of European Heating, Ventilation and Air Conditioning Associations (REHVA) [7] published several documents on the use of buildings under the spread of COVID-19 infection, in which the importance of improving ventilation systems and increasing the ventilation rate is mentioned. Zehng et al [8], Pan et al [9], Elsaid et al [10], and Berry et al [11] refer to the above reports by ASHRAE, RHEVA, SHASE, etc., and clarify the problems of the current air conditioning systems and suggest possible countermeasures and future design methods. In cold-climate regions with severely cold winters, increasing the ventilation rate by opening windows in winter increases the heating load for ventilation.…”
Section: Introductionmentioning
confidence: 99%